Simbol Kesenian Kuda Lumping Bagi Masyarakat Di Kelurahan Gunung Lengkuas - Dwi Rizky Wahyudi; Sri Wahyuni; Rahma Syafitri (Student Research Journal, 2023)
Kuda Lumping is a dance art in which in the performance process there are several things which are symbolized by mystical things, namely the ritual of burning incense, offerings of offerings and attractions of trance. The purpose of this study is to find out how the symbol of the Kuda Lumping art is for the people in Gunung Lengkuas Village. In this study the theory used by researchers is the Symbolic Interactionist theory. The method used in this study uses a descriptive-qualitative method which examines the artistic symbols of the Kuda Lumping for the people in Gunung Lengkuas Village. by using purposive sampling technique. Based on the results of the study, the researcher found that with the process contained in the Kuda Lumping performance where the community symbolizes that the things contained in the Kuda Lumping performance process are offering sesajen, burning kemenyan and the attraction of kesurupan is symbolized as mystical, thus an assumption or the meaning in society regarding the Lumping Horse is different which of course this is closely related to symbolic interactionism, where individuals or society in interpreting or assuming something based on creation through an interaction process which then chooses, evaluates, thinks, classifies and transforms the meaning of an object. So that in interpreting the art of Kuda Lumping it goes through an interaction process which then the individual concludes. In the community of the Gunung Lengkuas sub-district, 2 different meanings have been created regarding the Lumping Horse, namely the first, the Lumping Horse as entertainment and the Lumping Horse as a Mystical performance.